New avenues for second-line treatment of metastatic non-small-cell lung cancer. Issue 1 (January 2009) - Gridelli, Cesare; Maione, Paolo; Rossi, Antonio; Falanga, Marzia; Bareschino, Marianna; Schettino, Clorinda; Colantuoni, Giuseppe; Guerriero, Ciro; Nicolella, Dario; Rossi, Emanuela; Ferrara, Marianna Luciana; Palazzolo, Giovanni
Platinum-based doublets are the standard first-line therapy for patients with advanced non-small-cell lung cancer, with approximately a third of patients obtaining an objective response with first-line chemotherapy and another 20–30% achieving temporary disease stabilization. However, all patients inevitably experience disease progression. Three agents are approved for treating patients who progress after one prior regimen: docetaxel, pemetrexed and erlotinib. Erlotinib is the only agent approved for use in the third-line setting. Although these agents have yielded similar outcomes in terms of anti-tumor activity and efficacy, they have different toxicity profiles, and some factors that can help in the choice among them have begun to emerge, such as smoking history and histotype. Several new molecularly targeted agents have shown activity in Phase II trials and may be integrated into second-line therapy as single agents or in combination with current agents in the future. In particular, the most encouraging data in this clinical setting have been reported with the antiangiogenetic drugs bevacizumab (already approved for use in the first-line setting), vandetanib and sunitinib. Phase III trials with these agents are ongoing.